Hypertension in pregnancy - Broughton Pipkin, F; Roberts, JM (Journal of human hypertension, 2000)
Hypertension arising during pregnancy remains one of the two most frequently-cited causes of maternal death in the UK. In some cases, pregnancy is unmasking underlying hypertension, which manifests itself in later life. Pregnant women who develop de novo proteinuric hypertension (pre-eclampsia, PE) can share many risk factors with patients with the metabolic syndrome, such as obesity, dyslipidaemia and insulin resistance. However, more than half the women who develop PE remain normotensive thereafter. There is a genetic component(s) to the disease, but it is most improbable that there is a 'PE gene'. Rather, there are factors such as genetically-determined thrombophilias which are predisposers but not prerequisites. Impaired placentation is a feature, with inadequate invasion of the spiral arteries by syncytiotrophoblast and poor remodelling. However, similar features are found in association with non-hypertensive fetal growth restriction. Prospective studies have suggested a hyperdynamic circulation in early pregnancy, with cardiac output only falling in established disease. Baroreflex sensitivity is decreased in normal pregnancy, and still further decreased in established PE. Activation of endothelial cell function antedates the clinical diagnosis, and has features in common with atherosclerosis. Dyslipidaemia is common in PE and, via oxidation of susceptible lipids, may contribute to endothelial activation. Oxidative 'stress' is increased in PE, perhaps through a variant of the hypoxia-reperfusion phenomenon in the developing intervillous spaces. Such early changes might then lead to the clinically-evident syndrome in susceptible women. PE is a protean, multisystem, multifactorial disease, the causes of which are only slightly less enigmatic than a decade ago.